A model of facilitative communication for support of general hospital nurses nursing mentally ill people - TR Mavundla; M Poggenpoel; A Gmeiner (Curationis (Pretoria), 2001)
Part 1 of this article dealt with a full description of the research design and methods. This article aims at describing a model of facilitative communication to support general hospital nurses nursing the mentally-ill. In this article a model of facilitative communication applicable to any general hospital setting is proposed. Fundamental assumptions and relationship statements are highlighted and the structure and process of facilitative communication is described according to the three steps employed: 1) assisting the general hospital nurse learn the skill; 2) assisting the general hospital nurse practise the skill in order to develop confidence; and 3) using the skill in a work setting. The guidelines for operationalising this model are dealt with in the next article. The evaluation of the model is also briefly described.